Settlement of Patient Data Protection Disputes in Hospitals According to Law Number 27 of 2022 concerning Personal Data - Sasmiwati, Desi; Herisasono, Adi; Vitrianingsih, Yeni; Hardyansah, Rommy (IHSA Institute, 2025)
his study was conducted because there were several doubts about the security of patient personal data in the implementation of electronic medical records; leaks that were worried included, first, insurance applications requiring the transmission of patient data using electronic communication, second, patient data leakage through human resources at health facilities who deliberately photographed or provided patient data to other parties, and third, the occurrence of system leaks, one of which was due to a virus. This research aims to resolve disputes over patient data protection in health facilities by law Number 27 of 2022 Article 4 paragraph 2 concerning personal data protection. The research method used in this study is an empirical law approach. Based on the results of the study, it can be concluded that the protection of patient privacy data in the process of applying for insurance/guarantee at Health Service Facilities has been protected by law, and this is legally done in the process made well with a sophisticated system, even recently there has been a special electronic message for health facilities called to restore. Indeed, not all health facilities can use it